1985
DOI: 10.1128/aem.49.3.709-710.1985
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of nuclear polyhedrosis virus (Baculovirus subgroup A) by monochromatic UV radiation

Abstract: Monochromatic radiation at wavelengths of 290, 300, 310, and 320 nm inactivated occluded nuclear polyhedrosis virus of the Douglas-fir tussock moth, Orgyia pseudotsugata (McDunnough). Data indicate that all of the wavelengths are capable of causing virus inactivation; much greater fluences are needed for virus inactivation as the wavelength increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…However, Griego and Spence (1978) found that the greatest kill of spores occurred at 400 nm in the visible range because of its much greater amount of energy compared with 3.4.4 Sunscreens 67 light of shorter wavelengths. The mediumwave or erythermal UV band (UVB, 280-320nm) is the most important photoinactivator of baculovirus, with considerable but slower effect in the near-UV region (UVA 320-360 nm), and in some cases some effect above this (David, 1969;Timans, 1982;Griego et al, 1985;Martignoni and Iwai, 1985;Killick, 1986;Jones et al, 1993b). Light of some longer wavelengths, however, may be beneficial to microorganisms (Jones et al, 1993b).…”
Section: 44a Damaging Wavelengths In Sunlightmentioning
confidence: 99%
“…However, Griego and Spence (1978) found that the greatest kill of spores occurred at 400 nm in the visible range because of its much greater amount of energy compared with 3.4.4 Sunscreens 67 light of shorter wavelengths. The mediumwave or erythermal UV band (UVB, 280-320nm) is the most important photoinactivator of baculovirus, with considerable but slower effect in the near-UV region (UVA 320-360 nm), and in some cases some effect above this (David, 1969;Timans, 1982;Griego et al, 1985;Martignoni and Iwai, 1985;Killick, 1986;Jones et al, 1993b). Light of some longer wavelengths, however, may be beneficial to microorganisms (Jones et al, 1993b).…”
Section: 44a Damaging Wavelengths In Sunlightmentioning
confidence: 99%
“…It is made The copyright holder for this preprint this version posted March 23, 2021. ; https://doi.org/10.1101/2021.03.22.436482 doi: bioRxiv preprint Besides host density, other aspects of the local environment may affect viral transmission and dynamics in the field (Cory & Myers, 2003). In particular, ultraviolet radiation has been shown to inactivate viruses of all kinds (Sagripanti & Lytle, 2007), including baculovirus occlusion bodies (Griego, Martignoni, & Claycomb, 1985;Witt & Stairs, 1975). In field studies, examination of the presence of baculovirus occlusion bodies on shaded vs. unshaded foliage suggested that sunlight on leaves may inactivate viruses (Olofsson, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Two important limitations to the efficacy of this bioinsecticide relate, first, to the proportion of larvae that can be directly infected by the applied inoculum and, second, to the inactivation of the virus by UV solar radiation, a recognized problem for all biological insecticides (Ignoffo et al, 1977;Griego et al, 1985;Cohen et al, 1991;Inglis et al, 1995). To achieve a high prevalence of infection of larvae, it would be necessary to apply higher concentrations of virus, the costs of which would be prohibitive for a bioinsecticide targeted at impoverished maize growers.…”
Section: Introductionmentioning
confidence: 99%